Faktor yang Berhubungan dengan Keluhan Musculoskeletal Disorders(MSDs) pada Pengendara Ojek Online - Sunardi Sunardi; Asma Wati; Alchamdani Alchamdani; Ahmed Ayathollah (FORIKES, 2021)
Online motorcycle taxi drivers are a group of workers who are at high risk of musculoskeletal disorders caused by several risk factors, including occupational factors (work posture, frequency, duration, force or load, mechanical stress and repetitive movements), environmental factors (vibration, temperature, lighting, and work area) and individual factors (age, gender, years of service, smoking habits, sports activities and anthropometry also contribute to the occurrence of MSDs). The World Health Organization states that musculoskeletal conditions are the second largest contributor to disability in the world, with low back pain being the leading cause of disability globally. This study aims to analyze the factors associated with complaints of musculoskeletal disorders (MSDs) in online motorcycle taxi drivers in Kendari City. This research was quantitative using analytic method with cross sectional research design. The sample in this study was 88 people who were obtained using the accidental sampling technique and carried out in October at the community base for “ojek online” riders in Kendari City. Analysis of the data used was Chi-square test. The results showed that there was a relationship between smoking habits (p-value=0.003) and duration of work (p-value=0.004) with complaints of musculoskeletal disorders. However, there is no relationship between years of service (p-value=0.174) and workload (p-value=0,370) with complaints of musculoskeletal disorders.Keywords: smoking habits; work period; duration of work; workload; musculoskeletal disorders complaintsABSTRAKPengendara ojek online adalah kelompok pekerja yang berisiko tinggi terhadap musculoskeletal disorders yang disebabkan oleh beberapa faktor risiko antara lain faktor pekerjaan (postur tubuh saat bekerja, frekuensi, durasi, gaya atau beban, stres mekanik dan gerakan berulang), faktor lingkungan (getaran, suhu, pencahayaan, dan area kerja) dan faktor individu (umur, jenis kelamin, masa kerja, kebiasaan merokok, aktivitas olahraga dan antropometri juga ikut berkontribusi terhadap terjadinya keluhan MSDs). World Health Organization menyatakan kondisi musculoskeletal adalah penyumbang disabilitas terbesar kedua di dunia, dengan nyeri punggung bawah menjadi penyebab utama kecacatan secara global. Penelitian ini bertujuan untuk menganalisis faktor yang berhubungan dengan keluhan musculoskeletal disorders (MSDs) pada pengendara ojek online. Jenis penelitian ini adalah penelitian kuantitatif menggunakan metode analitik dengan rancangan penelitian cross sectional. Sampel dalam penelitian sebanyak 88 orang yang diperoleh secara Accidental sampling dan dilaksanakan pada bulan Oktober bertempat di pangkalan komunitas pengendara ojek online di Kota Kendari. Analisis data yang digunakan adalah analisis Chi-Square. Hasil penelitian menunjukkan ada hubungan antara kebiasaan merokok (Pvalue=0,003) dan durasi kerja (Pvalue=0,004) dengan keluhan musculoskeletal disorders. Namun tidak ada hubungan antara masa kerja (Pvalue=0,174) dan beban kerja (Pvalue=0,370) dengan keluhan musculoskeletal disorders.Kata kunci: kebiasaan merokok; masa kerja; durasi kerja; beban kerja; keluhan musculoskeletal disorders